Praktik Sosial-Politik Birokrasi Pemerintahan dalam Pemilukada di Indonesia: Perspektif Teori Strukturasi - Johansyah, Olan Nur Rakhmat; Yakub, Andi; Kambo, Gustiana Anwar (LP2M IAIN Palopo, 2023)
The expectation of reform for the bureaucracy remains neutral in elections and still encounters structural conflicts inherent in the bureaucracy as an agency. In the context of local politics, the government bureaucracy plays a crucial role in influencing the results of the regional elections. This article employs Anthony Giddens' theory of structuration to examine the strategic behaviour of the Indonesian government bureaucracy in regional elections. The data collection method used in this study was literature research, which aimed to gather data and information using various materials available in the library. The results of this study found that the bureaucracy involved in regional elections is at the level of discursive and practical consciousness, which originates from the bureaucracy's ability to reflect on itself and monitor similar practices in broader space and time. Integrating space and time in social practices is fundamental in observing agents' actions in interacting with the structure. The room and time of the regional elections are closely related to the space and time of governance.